5G and beyond : the future of IoT - Chatterjee, Parag, 1992-; Bhadoria, Robin Singh; Pathak, Yadunath (Boca Raton, FL : Chapman & Hall/CRC Press, 2022)
"Internet of Things (IoT) is one of the most trending topics in the tech-world. With its extensive reach, IoT is reshaping several areas like healthcare, transports, industries and more. The proposed book is a one-stop solution with all topics of IoT-5G in one place with adequate technical details This book is aimed primarily at post graduate students and researchers working in the field of Internet of Things (IoT). Researchers working in the field of advanced mobile communications for IoT and applied areas of IoT like Smart Cities, Smart Transports and eHealth will find this book significantly helpful"--
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things; 5G mobile communication systems; COMPUTERS / Computer Engineering; COMPUTERS / Networking / General; COMPUTERS / Networking / Security